EFFECTIVENESS OF CHILDHOOD IMMUNIZATION IN CONDITIONS MEASLES OUTBREAK - Вострикова, Ирина; Домитращук, Иванка; Мельничук, Лариса (SWorldJournal, 2020)
Statistical data on the incidence of measles, the implementation of the volume of vaccination of children, the analysis of the vaccine status of children with measles. Since the beginning of 2020, only 27 cases of measles have been registered (intensive